Surface-bound norbornylogous bridges as molecular rulers for investigating interfacial electrochemistry and as single molecule switches - Darwish, Nadim; Paddon-Row, M.; Gooding, J. (2014)
Electron transfer (ET) reactions through molecules attached to surfaces, whether they are through single molecules or ensembles, are the subject of much research in molecular electronics, bioelectronics, and electrochemistry. Therefore, understanding the factors that govern ET is of high importance. The availability of rigid hydrocarbon molecular scaffolds possessing well-defined configurations and lengths that can be systematically varied is crucial to the development of such devices.In this Account, we demonstrate how suitably functionalized norbornylogous (NB) systems can provide important insights into interfacial ET processes and electrical conduction through single molecules. To this end, we created NB bridges with vic-trans-bismethylenethiol groups at one end so they can assemble on gold electrodes and redox species at the distal ends. With these in hand, we then formed mixed self-assembled monolayers (SAMs) containing a small proportion of the NB bridges diluted with alkanethiols. As such, the NB bridges served as molecular rulers for probing the environment above the surface defined by the diluent species. Using this construct, we were able to measure the interfacial potential distribution above the diluent surface, and track how variation in the ionic distribution in the electrical double layer impacts ET kinetics.Using the same construct, but with a redox molecule that remains neutral in both oxidized and reduced states, we could explore the impact of the chemical environment near a surface on ET processes. These results are important, because with conventional surface constructs, ET occurs across this interfacial region. Such knowledge is therefore relevant to the design of molecular systems at surfaces involving ET. With a second family of molecules, we investigated aspects of single-molecule electrical conduction using NB bridges bearing vic-trans-bismethylenethiol groups at both ends of the bridge. This gave us insights into distance-dependent electron transport through single molecules and introduced a method of boosting the conductance of saturated molecules by incorporating aromatic moieties in their backbone. These partially conjugated NB molecules represent a new class of molecular wires with far greater stability than conventional completely conjugated molecular wires. Of particular note was our demonstration of a single molecule switch, using a NB bridge containing an embedded anthraquinone redox group, the switching mechanism being via electrochemically controlled quantum interference.